Trend of Rainfall Indices at Kg. Kedaik Station, Pahang - Syafrina, A.H.; Badron, K.; Norzaida, A. (Communications in Mathematics and Applications, 2018)
Malaysia has been constantly facing massive floods caused by excessive weather events during monsoon and inter-monsoon seasons. Major concerns on the consequences of flood include structural and erosional damage, loss of life and property and disruption of socio-economic activities. Mitigation efforts require proper planning, relying on credible quantification of such changes. The eastern part of Peninsular Malaysia is frequently affected by severe floods especially during north east monsoon season. Affected area includes Pahang state which is located in the middle and more towards the eastern part of Peninsular Malaysia. As such, this study examine the trend of rainfall indices to have a better understanding on rainfall distribution within the area. In particular, the performance of Gamma and Weibull distributions incorporated in Neyman Scott Rectangular Pulse model in reproducing rainfall indices was assessed at Kg. Kedaik station in Pahang. The trends of indices based on thirty years data were calculated and analysed using non-parametric, Mann Kendall test. Performance of both probability distributions was compared using Root Mean Square Error criteria. Results suggest that Gamma is the better distribution in reproducing the hourly rainfall series for Kg. Kedaik station. Further analysis indicate Gamma able to replicate the key rainfall characteristics such as the total amount of rainfall, mean rainfall amount on wet days or rainfall intensity, including the extreme indices; frequency of wet days exceeding the 95th percentile and rainfall intensity exceeding the 95th percentile. Meanwhile, the calculated trend in this study is consistent with previous studies, indicating the presence of positive trend at Kg. Kedaik station.